2022
DOI: 10.21203/rs.3.rs-1698826/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of Extended Spectrum Beta Lactamase and molecular detection of blaTEM, blaSHV and blaCTX-M genotypes among Gram Negative Bacilli Isolates from Pediatric Patient Population in Gaza strip

Abstract: Background: Extended-spectrum β lactamases (ESBLs) have the ability to hydrolyze and cause resistance to types of the β-lactam antibiotics, including the extended-spectrum (or third generation) cephalosporins (e.g., cefotaxime, ceftriaxone, ceftazidime) and monobactams (e.g., aztreonam).Objectives: To assess the prevalence and molecular characteristics of ESBL producing Gram negative bacilli, isolated from a cohort of pediatric patients in Gaza hospitals.Methods: A total of 322 isolates of Gram-negative bacil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(32 reference statements)
2
1
0
Order By: Relevance
“…(17.65%), and E. coli (14.71%), followed by S. aureus (13.72%). Bla SHV in our findings was around 18(47.3%) from total isolates ,several previous studies in compatible with our results , in a study conducted for Clinical Isolates of Enterobacteriaceae in Sudan by (30) , they revealed that 44% of the isolates produced bla SHV gene ; another study similar in some extent to our findings including : (31), in which SHV (43.1%) ; other study which conducted in Gaza by (32),they reported that 38.3% of Enterobacteriaceae isolates were harbored bla SHV gene ; (33) incompatible with our findings ,they summarized that much lower percentage than our findings around 5.1% .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…(17.65%), and E. coli (14.71%), followed by S. aureus (13.72%). Bla SHV in our findings was around 18(47.3%) from total isolates ,several previous studies in compatible with our results , in a study conducted for Clinical Isolates of Enterobacteriaceae in Sudan by (30) , they revealed that 44% of the isolates produced bla SHV gene ; another study similar in some extent to our findings including : (31), in which SHV (43.1%) ; other study which conducted in Gaza by (32),they reported that 38.3% of Enterobacteriaceae isolates were harbored bla SHV gene ; (33) incompatible with our findings ,they summarized that much lower percentage than our findings around 5.1% .…”
Section: Discussionsupporting
confidence: 92%
“…The recent study reported that blaSHV from all E.coli isolates about 26.3% and ( 29.4%,27.27,20%) in all groups respectively , this is in agreement with a study conducted in Erbil City, Iraqi Kurdistan Region by (34),they reported the presence of blaSHV in about (28.5%) of E.coli isolates ; Another study supported our findings was done by (32) investigated that around 20.6% of E. coli isolates had blaSHV; Additionally, (35)revealed that the rate of blaSHV around 20% ; The rate of blaSHV in this study was higher than that reported by (36) in an Iranian hospital (5.5%) which were E. coli isolates.…”
Section: Discussionsupporting
confidence: 92%
“…Plasmidderived beta-lactamases such as TEM-1, TEM-2, and SHV-1 are common enzymes among members of the Enterobacteriaceae and are transferred to other bacteria via plasmids. Although ESBL enzymes are mainly derived from TEM and SHV enzymes, new plasmid-derived ESBLs such as CTX-M, OXA-1, PER-1, and PER-2, which are not from TEM and SHV, have also been identified [22][23][24].…”
Section: Discussionmentioning
confidence: 99%